Towards an Inclusive Campus: Exploring the Physical and Non-Physical Challenges for Students with Disabilities in Higher Education - Khairun Nisa; Lailatussaadah Lailatussaadah (Nurul Jadid University, 2025)
This study aims to analyze accessibility for people with disabilities in higher education, focusing on both physical and non-physical dimensions as part of inclusive campus policies. A qualitative approach was used, employing interviews, observations, and document reviews of campus policies and facilities. The results show that, in the physical aspect, several facilities, such as ramps, accessible toilets, and wheelchairs, have been provided in the main buildings. However, issues such as limited distribution, the lack of elevators, and outdated building designs that do not meet universal design standards hinder mobility and academic participation. In terms of non-physical accessibility, the institution has established a Disability Service Unit and a social inclusion unit as part of its commitment. Informal social support from lecturers and peers is also available, though there is a shortage of professional assistants. There is a need for enhanced training, policy coordination, and a more inclusive organizational structure. The implications of this research provide policy recommendations based on social models and universal design principles to improve inclusive campuses. Future research could expand to comparative studies at the national level.